A Review of Extraterrestrial Organic Carbon and its Potential Impact on Life on Earth - Yarkasih, Firza Riyadhini; Nurita, Tutut; Al-Zahzamri, Nariyah; Pratiwi, Riska Ayu; Khasanah, Nur (Universitas Islam Negeri (UIN) Mataram, 2024)
The universe is a space containing large amounts of both organic and inorganic carbon that has the potential to encourage heterotrophs on habitable planets. Meteorites are materials that can transport carbon from outer space to the planet's surface. Meteorites bombarded the Earth's surface during the early days of evolution and proliferation of life, potentially providing a source of abiotic organic carbon to support early life. This study aims to analyze research methods used in detecting the use of space organic carbon, analyze research results related to the role of space organic carbon, and provide further understanding to the researchers associated with organic carbon from space and its potential in human life on Earth. This study uses a systematic review method using 15 sources of information from national and international news and journal articles related to space organic carbon and its potential. This study showed that extraterrestrial organic carbon produces a source of carbon that is beneficial for microorganisms to integrate into their proteins. Combining inverse stable isotope labeling and infrared spectroscopy shows that organic carbon from Aguas Zarcas carbon chondrite can be harnessed for cell growth. Previous discoveries have also shown that aerobic microbial communities have potential in human space settlement plans to access and research carbonaceous asteroid material.